Probiotics and vaginal microecology: fact or fancy? - Laura Buggio; Edgardo Somigliana; Alessandra Borghi; Paolo Vercellini (BMC, 2019)
Abstract Background Probiotics are live microorganisms that, when administered in adequate amounts, should confer a health benefit to the host. Media sources tend to present probiotics as an appealing health promotion method able to prevent or treat a wide variety of clinical conditions. In obstetrics and gynaecology, Lactobacilli species are mainly used to restore the physiologic vaginal microbiota in order to treat bacterial vaginosis and vulvovaginal candidiasis (VVC) and prevent preterm birth. Discussion Several RCTs investigated the potential benefits of probiotics in gynaecological and obstetrics conditions. For all potential indications, recent specific meta-analyses have been published. Considering vulvovaginal candidiasis in non-pregnant women, probiotics slightly improved the short-term clinical and mycological cure, and reduced the 1-month relapse. However, no important impact of probiotic use was observed on long-term clinical or mycological cure. Similarly, the addition of probiotics to metronidazole for the treatment of bacterial vaginosis was not shown to provide any additional benefit. In obstetrics, using probiotics during pregnancy neither decreased nor increased the risk of preterm birth before 34 weeks or before 37 weeks. Similarly, no benefits emerged for gestational diabetes, preterm premature rupture of membrane, and small and large for gestational age infants. Conclusion Despite increasing marketing of probiotics for the treatment of vulvovaginal candidiasis and prevention of preterm birth robust evidence demonstrating a beneficial effect is scarce. Moreover, there was considerable heterogeneity among the different studies in terms of route of administration, strain/s of probiotic adopted, and length of probiotic use. Before recommending the systematic use of probiotics to treat bacterial vaginosis and VVC and prevent preterm birth, high-quality research is needed. Professional medical associations should issue recommendations defining if, when, and how probiotics should be used for gynaecological disorders.